Prior Exception To Mediation Agreement In Ecuador - Galán Melo, Gabriel Santiago; Almeida, Juan Fernando (Universidad Hemisferios, 2024)
This paper analyzes the prior exception of the existence of mediation agreement provided for all types of judicial proceedings regulated by the Código Orgánico General de Procesos -COGEP-, its procedural implication and the inconveniences it has generated in Ecuador at the time of its resolution due to its legal unspecified configuration unduly assimilated to the commitment or arbitration agreement and the interpretation made of this by the Corte Nacional de Justicia -CNJ- through Resolution No. 12-2017, which improperly treats the existence of mediation agreement as a prior non-curable exception of substantial implication. Inadequate treatment that ends up articulating -apparently- on the one hand, an unreasonable obstacle of access to justice, since, it would force the judge to inhibit himself from a legitimate cause despite the manifest current absence of cooperative willingness to mediate of those involved in the dispute; and, on the other hand, creating an irregular space of uncertainty regarding the effects that procedurally could produce such inhibition since, having to be resolved through a judgment -according to the provisions of the binding judicial criterion-, it should cause prima facie, res judicata. If this were so, it would in fact generate an unreasonable obstacle to access to justice that would be irreparable.